PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN KESEHATAN MENTAL SISWA KELAS X IIS SMA NEGERI 12 PEKANBARU - Kurnia Wulandar Wulandar; Tri Umari Umari; Raja Arlizon Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This study aims to determine the effect of guidance services group for mental hygiene improvement high school students in grade X IIS Negeri 12 Pekanbaru.the method used was experimental method. To collect the data used purposive sampling technique. The subjects were high school students in grade X IIS Negeri 12 Pekanbaru were 30 students. The results showed that guidance services group can improve the mental hygiene of students. This is evident from analysis of the value of is greater than t table with a significant level of 5% (13,48>2,000). Thus ho rejected and ha accepted.which means there is a significant difference to the improvement of mental hygiene of students before the guidance given after the guidance services group. Key Words: guidance services group, Mental Hygiene